ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DAN DAMPAKNYA TERHADAP HARGA SAHAM (Studi Pada Perusahaan Go Public yang Terdaftar di BEI Periode Tahun 2010-2102) - Theya, Gabriella Tiffany (Universitas Sam Ratulangi, 2014)
In stock investing in the stock market, investors need to have information on the factors triggering changes in stock prices. One possible trigger factor is the amount of dividends paid by the company. The shareholders as investors expect the yield of the company in the form of dividends and capital gains. Determination of the distribution of dividends is an interesting problem because it will meet the expectations of investors, on the other hand the policy is not to inhibit the growth let alone threaten the survival of the company.The purpose of this study was to determine the factors that influence the dividend policy and its impact on the stock price. The study population was all companies listed in Indonesia Stock Exchange in 2010-2012, as many as 331 companies. By using judgment sampling method then obtained a sample of 86 companies.The analytical method used is the method of path analysis (path analysis) to analyze the pattern of relationships between variables in order to determine the effect of directly or indirectly, a set of independent variables (exogenous) on the dependent variable (endogenous). As for the study of data processing using SPSS version 19.0.The results show the tax burden has a positive effect and no significant effect on dividend policy, liquidity and debt policy has a negative effect and no significant effect on dividend policy, profitability and firm size has a positive and significant effect on dividend policy, while simultaneously variables affecting significant effect of dividend policy. For a direct influence on stock prices, the tax burden has a positive influence and insignificant, liquidity and debt policies have a significant positive influence and not, as well as profitability, firm size and dividend policy has a positive and significant impact, while simultaneously, the variables that affect stock prices have a significant effect.